2020
DOI: 10.1182/blood.2019001903
|View full text |Cite
|
Sign up to set email alerts
|

High-parametric evaluation of human invariant natural killer T cells to delineate heterogeneity in allo- and autoimmunity

Abstract: Human invariant natural killer T (iNKT) cells are a rare innate-like lymphocyte population that recognizes glycolipids presented on CD1d. Studies in mice have shown that these cells are heterogeneous and are capable of enacting diverse functions, and the composition of iNKT cell subsets can alter disease outcomes. In contrast, far less is known about how heterogeneity in human iNKT cells relates to disease. To address this, we used a high-dimensional, data-driven approach to devise a framework for parsing huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…We did not identify any clear enrichment of iNKT17-signature expressing cells in either cluster 0 or cluster 1 (Figure 3, bottom panel). To further validate the iNKT-sublineages signatures we generated, we next assessed them on publicly available scRNA-seq data of iNKT cells isolated from human peripheral blood (Erkers et al, 2020). Our analysis clearly identified a cluster of iNKT cells displaying an enrichment in iNKT1-signature genes (Supplemental Figure 2A,B) while we observed the presence of some cells enriched in iNKT2- and iNKT17-signature genes not associated with any specific cluster.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not identify any clear enrichment of iNKT17-signature expressing cells in either cluster 0 or cluster 1 (Figure 3, bottom panel). To further validate the iNKT-sublineages signatures we generated, we next assessed them on publicly available scRNA-seq data of iNKT cells isolated from human peripheral blood (Erkers et al, 2020). Our analysis clearly identified a cluster of iNKT cells displaying an enrichment in iNKT1-signature genes (Supplemental Figure 2A,B) while we observed the presence of some cells enriched in iNKT2- and iNKT17-signature genes not associated with any specific cluster.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudotime analysis was performed using the Monocle3 package. Previously published scRNA-seq datasets from human iNKT cells recovered from the peripheral blood (PRJNA563899, PRJNA565590; (Erkers et al, 2020)) were analyzed using the same pipeline. 2020) showing distinct clusters of human iNKT cells from peripheral blood.…”
Section: Single Cell Rna Sequencingmentioning
confidence: 99%
“…Recently, Erkers et al 38 reported an extensive characterization of human iNKT heterogeneity and identified a CD4 -CD94 1 population with iNKT1-like properties and a CD4 1 population producing higher levels of IL-4. Due to the paucity of iNKT cells in human peripheral blood, current clinical trials using iNKT cells involve in vitro expansion protocols (#NCT03605953).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to their murine counterparts, most human iNKT cells express PLZF ( 80 82 ), and are characterized by an innate-like transcriptional profile that results in a “poised-effector” status allowing them to rapidly mediate functional responses ( 83 ). Multi-parameter flow cytometric analyses and gene expression studies have revealed human iNKT cells to express a diverse selection of cytokines and chemokines ( 84 88 ). Human iNKT cells can be segregated into two major subsets according to CD4 expression ( 84 , 85 ).…”
Section: What Determines the Nature Of The Functional Response Mediat...mentioning
confidence: 99%